2017
DOI: 10.1016/j.jid.2016.08.037
|View full text |Cite
|
Sign up to set email alerts
|

Glycyrrhizin Ameliorates Fibrosis, Vasculopathy, and Inflammation in Animal Models of Systemic Sclerosis

Abstract: Systemic sclerosis (SSc) is a multisystem inflammatory and vascular disease resulting in extensive tissue fibrosis. Glycyrrhizin, clinically used for chronic hepatic diseases and itching dermatitis, modulates the pathological processes of inflammation, vasculopathy, and fibrosis in human diseases and their animal models. Therefore, we investigated a potential impact of glycyrrhizin on the key pathological manifestations of SSc, including inflammation, vasculopathy, and tissue fibrosis, with bleomycin-treated m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 39 publications
2
30
0
Order By: Relevance
“…Its expression was significantly increased in a variety of skin diseases, such as psoriasis, alopecia areata, vitiligo, atopic dermatitis, Henoch‐Schönlein purpura (HSP), pemphigus, and drug‐induced hypersensitivity syndrome/drug reaction with eosinophilia and systemic symptoms (DRESS) . Due to the similar pharmacological efficacy to corticosteroids but with milder side effects, Glycyrrhizin has been widely utilized in several dermatologic disorders for many years, such as active‐stage generalized vitiligo, psoriasis, alopecia areata, and is also reported to be effective in alleviating the symptoms of atopic dermatitis and systemic sclerosis in animal model . Based on the clinical observation that patients with recalcitrant Riehl’s melanosis may present with facial erythema and itching, which are signs of local inflammation, we applied Glycyrrhizin compound 75 mg orally three times a day for all enrolled patients, aiming to alleviate the inflammatory reaction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Its expression was significantly increased in a variety of skin diseases, such as psoriasis, alopecia areata, vitiligo, atopic dermatitis, Henoch‐Schönlein purpura (HSP), pemphigus, and drug‐induced hypersensitivity syndrome/drug reaction with eosinophilia and systemic symptoms (DRESS) . Due to the similar pharmacological efficacy to corticosteroids but with milder side effects, Glycyrrhizin has been widely utilized in several dermatologic disorders for many years, such as active‐stage generalized vitiligo, psoriasis, alopecia areata, and is also reported to be effective in alleviating the symptoms of atopic dermatitis and systemic sclerosis in animal model . Based on the clinical observation that patients with recalcitrant Riehl’s melanosis may present with facial erythema and itching, which are signs of local inflammation, we applied Glycyrrhizin compound 75 mg orally three times a day for all enrolled patients, aiming to alleviate the inflammatory reaction.…”
Section: Discussionmentioning
confidence: 99%
“…[21][22][23][24][25] Due to the similar pharmacological efficacy to corticosteroids but with milder side effects, Glycyrrhizin has been widely utilized in several dermatologic disorders for many years, such as active-stage generalized vitiligo, 26 psoriasis, 27 alopecia areata, 28 and is also reported to be effective in alleviating the symptoms of atopic dermatitis and systemic sclerosis in animal model. 29…”
Section: Discussionmentioning
confidence: 99%
“…Glycyrrhizin significantly ameliorated dermal fibrosis in bleomycin-treated mice, which was partly attributable to blockade of TGF-β signaling in dermal fibroblasts through the downregulation of thrombospondin 1, a latent TGF-β receptor, and transcription factors Smad3 and Ets1. Furthermore, bleomycin-dependent induction of T helper type 2-skewed immune polarization, M2 macrophage infiltration, and EndoMT was greatly suppressed in mice administered glycyrrhizin [170].…”
Section: Ros ↑mentioning
confidence: 96%
“…High-mobility group box 1 (HMGB1) is a multifunctional protein that exerts pro-inflammatory activity by mainly binding to receptor for advanced glycation end products (RAGE). It has been reported that HMGB1 is released from immune cells, and contributes to inflammation, immune responses, myofibroblast differentiation, ECM production, and fibrosis progression [30][31][32][33][34], and the HMGB1 inhibitor, glycyrrhizin, attenuates the development of fibrosis in the belomycin-treated mice [35].…”
Section: Introductionmentioning
confidence: 99%